Identifying Chloris Species from Cuban Citrus Orchards and Determining Their Glyphosate-Resistance Status - Bracamonte, Enzo R.; Fernández-Moreno, Pablo T.; Bastida, Fernando; Osuna, María D.; Alcántara-de la Cruz, Ricardo; Cruz-Hipolito, Hugo E.; De Prado, Rafael (Frontiers in Plant Science, 2017)
The Chloris genus is a C4 photosynthetic species mainly distributed in tropical and subtropical regions. Populations of three Chloris species occurring in citrus orchards from central Cuba, under long history glyphosate-based weed management, were studied for glyphosate-resistant status by characterizing their herbicide resistance/tolerance mechanisms. Morphological and molecular analyses allowed these species to be identified as C. ciliata Sw., C. elata Desv. and C. barbata Sw. Based on the glyphosate rate that causes 50% mortality of the treated plants, glyphosate resistance (R) was confirmed only in C. elata, The R population was 6.1-fold more resistant compared to the susceptible (S) population. In addition, R plants of C. elata accumulated 4.6-fold less shikimate after glyphosate application than S plants. Meanwhile, populations of C. barbata and C. ciliata with or without glyphosate application histories showed similar LD50 values and shikimic acid accumulation rates, demonstrating that resistance to glyphosate have not evolved in these species. Plants of R and S populations of C. elata differed in 14C-glyphosate absorption and translocation. The R population exhibited 27.3-fold greater 5-enolpyruvyl shikimate-3-phosphate synthase (EPSPS) activity than the S population due to a target site mutation corresponding to a Pro-106-Ser substitution found in the EPSPS gene. These reports show the innate tolerance to glyphosate of C. barbata and C. ciliate, and confirm the resistance of C. elata to this herbicide, showing that both non-target site and target-site mechanisms are involved in its resistance to glyphosate. This is the first case of herbicide resistance in Cuba.